Effect of humidity on copper phthalocyanine films deposited at different gravity conditions. Issue 1 (3rd January 2017) - Karimov, Khasan S.; Ahmad, Zubair; Fatima, Noshin; Ahmed, Muhammad Mansoor; Abid, Muhammad
Abstract : Purpose: The paper aims to study the effects of humidity on the electrical properties of copper phthalocyanine (CuPc) thin films deposited at different gravity conditions. Design/methodology/approach: Surface-type samples were fabricated on glass substrates with preliminary-deposited copper electrodes. The CuPc solution was prepared in benzene. The thin films of CuPc were deposited on these substrates at diverse gravity conditions by drop-casting and centrifugation at 1 × g and 70 × g, respectively. Impedance and capacitance of the fabricated devices were measured against the different relative humidity ranging from 32 to 98 per cent. Findings: The impedance and the capacitance of the CuPc film were found to be dependent on the ambient humidity levels (32-98 per cent) and the gravity conditions (1 × g and 70 × g ) opted during the fabrication process. Research limitations/implications: The centrifugation technique can potentially be used in the instrumentation industry for the fabrication of humidity sensors. Practical implications: The results of the investigations can potentially be used in the instrumentation and optoelectronics industry for the fabrication of humidity sensors. Originality/value: CuPc films were deposited from a solution in benzene using drop-casting and centrifugation. The electrical properties of the films were found to be dependent on film fabrication conditions and ambient humidity levels. Growth-dependent electrical properties of the CuPc films can be explained by considering their structure.